Contemporary issues regarding cases of crimes against humanity as tried in the international criminal court / Abu Daud Abu Samah…[et al.] - Abu Samah, Abu Daud; Md. Top, Amalina Basirah; Quaj Mamandh, Mohd Khaidhir Khan; Abd. Rabim, Anis Nabila (2009)
This study concerns the contemporary issues regarding cases of crimes against humanity as tried in the International Criminal Court (ICC). There are a lot of questions regarding the complexity of the jurisdictional matters of the states and the ICC. In addition, there is a question of the application universal jurisdiction in the ICC Statute. When a state becomes a party to ICC, the state must surrender to the jurisdiction of the Court particularly in respect to the crimes listed in the ICC Statute. Based on the doctrine of State Sovereignty, most states are reluctant to surrender its official to be tried at the ICC. The argument of state immunity arises because states or its officials are immune from foreign states' prosecution. Therefore, the cooperation and legal assistance of the contracting parties to the ICC Statute are important. Whenever, a state refuses to surrender its official, it'll create problem and ineffectiveness of measures taken by the ICC.